Implementasi Akad Wadi'ah Pada Koperasi Simpan Pinjam dan Pembiayaan Syariah - Marlina, Vina; Sobarna, Nanang (Universitas Koperasi Indonesia, 2023)
This study aims to determine the implementation of the wadi'ah contract on wadi'ah savings products carried out by the Baitul Maal Wa Tamwil (BMT) Nusa Ummat (NU) Sejahtera branch of the Tanjungsari branch of the Sharia Financing and Savings Cooperative (KSPPS). KSPPS BMT NU Sejahtera is a sharia-based financial institution. KSPPS BMT NU Sejahtera offers a variety of products to meet the needs of the community, including raising funds including wadi'ah savings. This researcher uses a type of qualitative research with descriptive methods. Descriptive method is a method that describes and answers the problems of a phenomenon or event that occurs in the field or describes and describes findings in the field. The results of the research that has been done can be concluded that the implementation of the contract on wadi'ah savings at KSPPS BMT NU Sejahtera Tanjungsari branch can be said to be in accordance with sharia and the procedures carried out have been carried out properly